VALORIZING URBAN ARCHAEOLOGICAL HERITAGE: EVALUATING THE SUSTAINABLE MANAGEMENT OF TIPAZA’S SITE THROUGH THE RST02 GRID - Imane Kechacha,; Ammar Korichi,; Koudoua Ferhati, (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to evaluate the valorization of the archaeological heritage of Tipaza through the RST02 Grid, focusing on governmental, social, economic, environmental, and cultural dimensions. Using a questionnaire-based approach, 250 surveys were distributed to assess perceptions, challenges, and opportunities regarding the preservation and promotion of Tipaza’s archaeological site. The collected data is analyzed to highlight key factors affecting sustainable management and propose strategies to enhance the integration of urban and archaeological heritage within a sustainable development framework.